The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/ma10070698
|View full text |Cite
|
Sign up to set email alerts
|

A Combined High and Low Cycle Fatigue Model for Life Prediction of Turbine Blades

Abstract: Combined high and low cycle fatigue (CCF) generally induces the failure of aircraft gas turbine attachments. Based on the aero-engine load spectrum, accurate assessment of fatigue damage due to the interaction of high cycle fatigue (HCF) resulting from high frequency vibrations and low cycle fatigue (LCF) from ground-air-ground engine cycles is of critical importance for ensuring structural integrity of engine components, like turbine blades. In this paper, the influence of combined damage accumulation on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
86
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 38 publications
1
86
0
Order By: Relevance
“…Blades are important components in power and energy equipment. The formability of material and the complexity of structural shape are two key factors during the design and manufacture process of blades . In practical engineering, blades are often manufactured as smooth curved surface shapes to satisfy the performance requirements for harsh environment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Blades are important components in power and energy equipment. The formability of material and the complexity of structural shape are two key factors during the design and manufacture process of blades . In practical engineering, blades are often manufactured as smooth curved surface shapes to satisfy the performance requirements for harsh environment.…”
Section: Introductionmentioning
confidence: 99%
“…The formability of material and the complexity of structural shape are two key factors during the design and manufacture process of blades. [4][5][6] In practical engineering, blades are often manufactured as smooth curved surface shapes to satisfy the performance requirements for harsh environment. These smooth curved surface shapes can generate wake flow field, secondary flow, and boundary layer separation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under variable amplitude vibration (VAV), Kinyon and Hoeppner [13] concluded that Miner rule is insufficient to predict failure lives of Ti-6Al-4V with multiple load levels. Zhu et al [14] proposed a new damage accumulation model based on Miner rule to consider the coupled damage due to HCF-LCF interaction by introducing four load parameters, and results show that the proposed model provides good predictions. Mlikota et al [15] proposed a micro-model containing the microstructure of carbon steel to simulate the crack growth process, which shows an acceleration effect on short-crack growth rate due to overload.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that BPNN can be effectively used to predict the strain of unmeasured points of wind turbine blades.Energies 2019, 12, 1026 2 of 15 strain, stiffness, and deflection, and then provided more accurate stiffness data for a numerical model of load calculations for wind turbines. Thus, many achievements have been obtained in the blade load bearing capacity and parameter measurement methods, and some studies have also focused on structural characteristics and damage analysis of the blades [5][6][7][8][9][10][11][12]. Besides, some surrogate models for wind turbine blade stress/strain prediction due to the significant computational burden of physics-based simulation were constructed [13,14].…”
mentioning
confidence: 99%